The Return to Keynes - Calderón, Cuauhtémoc (Frontera Norte, 2017)
editado por Bradley W. Bareman, Toshiaki Hirai y Maria Cristina Marcuzzo, Cambridge, Massachusetts y Londres, The Belknap Press of Harvard University Press, 2010